KONSEP PENDIDIKAN ISLAM IKHWAN AS-SHAFA (Suatu Kajian analisis Kritis) - La Rajab (al-Iltizam: Jurnal Pendidikan Agama Islam, 2017)
khwan ash-Shafa is a bevy of peripatetic secret in the field of science field. As according to its the name Ikhwan ash-Shafa means "holy brotherhood and cleanness". Main ground of this bevy is candid and heartfelt brotherhood holy folk. Secrecy of this group, also names their x'self khulan al-wafa ' ahl adl and abna new al-hamd is expressed after in command of Dinasti Buwaiha, is understanding Syiah in Baghdad in the year 983 M. Ikhwan this ash-Shafa result masterpiece writes 52 brochures which they name Rasa'il Ikhwan As-Shafa'. He was popular Ensiklopedia about science and philosophy of the at that time. Evaluated from the angle of content, this Rasa'il earns in classification to become four areas that is, Mathematics, Physics and Natural philosophy, Psychology and Deism. Education concept of Ikhwan As-Shafa is more emphasizing atly the relation of spirituality. What studied shall practiced by the members. All attention in education must be aimed at adolescent because adolescent is susceptible age which if is not handled correctly will bring unfavourable impact, but if handled correctly, hence will bear good router generations and tough. Therefore, becomes basic thing for the adolescents paid attention to be guided and educated towards which are positive because they are router for taking place a nation and state. If when smart adolescent and tough, hence the taft state and nation and respected by state and other nations. By his its is in consequence is required the ready teachers to guide, educates and trains the the generations. Teacher intended is teacher which can inherit my values and prila examplizeed by Rasulullah Saw.